Phonemic contrasts under construction? Evidence from Basque. (3rd March 2020) - Larraza, Saioa; Molnar, Monika; Samuel, Arthur G.
Abstract: Attunement theories of speech perception development suggest that native‐language exposure is one of the main factors shaping infants' phonemic discrimination capacity within the second half of their first year. Here, we focus on the role of acoustic–perceptual salience and language‐specific experience by assessing the discrimination of acoustically subtle Basque sibilant contrasts. We used the infant‐controlled version of the habituation procedure to assess discrimination in 6‐ to 7‐month and 11‐ to 12‐month‐old infants who varied in their amount of exposure to Basque and Spanish. We observed no significant variation in the infants' discrimination behavior as a function of their linguistic experience. Infants in both age‐groups exhibited poor discrimination, consistent with Basque adults finding these contrasts more difficult than some others. Our findings are in agreement with previous research showing that perceptual discrimination of subtle speech sound contrasts may follow a different developmental trajectory, where increased native‐language exposure seems to be a requisite.